Service Access and Veterinarian Communication as Predictors of Cat Owners' Core Vaccination Compliance - Rafif Naufal Dani; Abdul Halim; Dadang Kusnadi (Research of Service Administration Health and Sains Healthys, 2026)
Core vaccination is a fundamental preventive service for maintaining cat health and limiting the transmission of infectious diseases with potential animal and public health consequences. Nevertheless, cat owners' adherence to recommended vaccination schedules remains a managerial challenge in veterinary clinics. This study examined the effects of service access and veterinarian communication on cat owners' compliance with core vaccination at Sukma Animal Care Veterinary Clinic, Wonosobo. A quantitative survey design was applied to 100 cat owners selected through purposive sampling. Data were collected using a structured five-point Likert questionnaire and analyzed with descriptive statistics and multiple linear regression. The findings showed high respondent perceptions of service access (mean = 4.03), veterinarian communication (mean = 3.92), and compliance (mean = 3.99). Regression analysis indicated that service access significantly predicted compliance (B = 0.496, beta = 0.480, p < 0.001), while veterinarian communication also had a significant positive effect (B = 0.508, beta = 0.478, p < 0.001). Simultaneously, both variables explained 44.3% of compliance variance (R2 = 0.443; F = 38.560; p < 0.001). The study concludes that improving accessible service systems and strengthening clear, empathetic, and interactive veterinarian communication are essential managerial strategies for increasing owner compliance with preventive vaccination programs.